External analysis of boundary points of convex sets: illumination and visibility - Moreno, José Pedro; Seeger, Alberto (MATHEMATICA SCANDINAVICA, 2009)
The purpose of this work is studying the geometry of the boundary K of a solid closed convex set K in a normed space. In a recent paper of ours, such a study has been carried out with the help of supporting cones and drops. Now, illuminated sets and visible sets are the main tools of analysis.